FORMATION OF PERSONNEL RESILIENCE CLUSTER IN THE STRUCTURE OF THE COMPETENCE MODEL AS A CONDITION FOR THE FORMATION OF PERSONNEL STABILITY IN THE TIME OF WAR - Вартанова, Олена В.; Повзун, Дмитро І. (Journal of Strategic Economic Research, 2024)
The essence and distinctive characteristics of personnel resilience as a prerequisite for fostering enterprise resilience during times of war, were studied. Staff resilience in corporate management is defined as an individual's capacity to maintain a stable level of physical and psychological health and well-being, ensuring consistent performance even in adverse conditions. The dual nature of maintaining personnel stability within enterprises is highlighted, evident across various levels of corporate management, notably at the corporate level (as reflected in the dynamics of the personnel management system and its stability indicators) and at the individual level (based on personal factors contributing to employees' mental stability). The need to investigate personal and professional dimensions of staff resilience within the integrated framework of staff competencies is justified. The overall structure of the "personnel resilience" cluster, within the enterprise's competency model, was delineated, along with the development of the corresponding competency cluster. This includes indicative behavioral indicators for each competency within the cluster, facilitating the assessment of personnel resilience as a competency attribute. The aim of the article is to explore the resilience of personnel as a cluster of competencies within the structure of the personnel competency model, serving as a condition for shaping the resilience of enterprise personnel during times of war. The methodological basis of the research includes scientific analysis and synthesis, ontology method, semantic analysis, competence approach, structural and logical analysis.